Effect of delay interval and cue focality on prospective memory - Zongbin Sun; Yu Tian; Tongxuan Dang; Qing Yang; Yunfei Guo; Yongxin Li (BMC Psychology)
Abstract Background Prospective memory refers to the ability to perform planned things in the appropriate future situations. Due to pointing towards the future, prospective memory usually has a certain amount of time delay. This study investigated the impact of a delay interval on prospective memory under different cue focality conditions and used the multinomial processing tree model to determine which component of prospective memory was affected. Methods Participants were assigned to 2-back delay group, no task delay group, or no-delay group, and then assigned to perform either focal prospective memory tasks or non-focal prospective memory tasks. Results The results showed that, compared to the non-delay group and no task delay group, participants in the 2-back delay group exhibited worse prospective memory performance, but better ongoing task performance after the delay interval task. The multinomial processing tree model analysis showed that the delay interval only affected the prospective component of prospective memory and had no impact on the retrospective component. Conclusions The results indicate that delay intervals affect the accuracy of prospective memory under different cue focality conditions. Meanwhile, delay intervals only impair the prospective component of prospective memory.